Creativity and gaze behaviour in football - Stephan Zahno (Bern Open Publishing, 2023)
Performing creative actions is considered a decisive element in football. Recent studies have suggested that football players' creativity is underpinned by a specific visual search strategy (e.g., Roca et al., 2021). Specifically, studies showed that players who scored high in a football-specific creativity task used more fixations of shorter durations than players who scored low. In the creativity task, players were asked to name as many solution ideas as possible. From an applied perspective, the questions arise: is this gaze strategy generally beneficial to perform creative actions? Should this gaze pattern be trained to improve creativity? In contrast to the idea of one single creativity-related gaze pattern, eye-tracking research in sports suggests that optimal gaze behaviour is highly dependent on situational task demands (Vater et al., 2020). Moreover, generally increasing the number of short fixations is expected to be dysfunctional to both motor accuracy and to the perception of task-relevant opportunities due to saccade-related costs. Accordingly, we hypothesized that many fixations of short duration are positively associated with players' ability to generate many ideas in the specific creativity task but not with performing creative actions. Fifteen footballers participated in an experiment with two conditions. In one condition (DT-condition), we replicated Roca et al.'s studies: participants stood in front of a large screen and with a ball in front of them. They were asked to view 20 videos of attacking situations and imagine themselves as the player in ball possession. At key moments of the situation, the videos were occluded. At this point, players' task was to physically play the ball and verbally confirm their decision. Subsequently, the last frame of the video reappeared, and their task was to name as many solution ideas as possible within 45 s. Moreover, a second condition was added (action-condition). While the first part of the task remained identical, the last frame did not reappear after playing the ball. In the action condition, the task-instruction was-as in a real game-to perform the most promising solution. In both conditions, eye tracking data were recorded. Results indicate that many fixations of short durations were linked to generating more ideas in the DT-condition-replicating Roca et al.'s (2021) finding-, however, not with performing creative solutions in the action-condition. As predicted, in the action-condition, the pattern was reversed: Players that performed more functional and creative actions used less fixations per second. For practice the results challenge the idea of training a specific creativity-related gaze pattern to improve creativity. Rather, our findings suggest that training should provide learning opportunities to acquire functional gaze strategies that are optimally adapted to situational task demands. References Roca, A., Ford, P. R., & Memmert, D. (2021). Perceptual-cognitive processes underlying creative expert performance in soccer. Psychological Research, 85(3), 1146-1155. https://doi.org/10.1007/s00426-020-01320-5 Vater, C., Williams, A. M., & Hossner, E.-J. (2020). What do we see out of the corner of our eye? The role of visual pivots and gaze anchors in sport. International Review of Sport and Exercise Psychology, 13(1), 81-103. https://doi.org/10.1080/1750984X.2019.1582082